Democratization of knowledge in times of pandemic among teachers - Solano-Barliza, Andrés D.; Aarón González, Marlin A.; Echeverría-King, Luisa F.; Deluque-Montaño, Olisney (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Information and Communication Technologies (ICT) have gained great relevance as a result of the health situation produced by Covid-19, so new dynamics in teacher training are proposed. The study is a descriptive qualitative study using case studies, content and discourse analysis. The teachers explain the adaptation of the technopedagogical design, motivating them to the proactive self-learning of their students. The pedagogical sense of the use of ICT provided a learning scenario to favor the enrichment of teachers’ practices, where the democratization of knowledge is achieved.